Peran Bimbingan Kelompok Dengan Permainan Gobak Sodor Untuk Membentuk Karakter Sosial Pada Anak Panti Asuhan Yatim Putri Aisyiyah II Surakarta - Eka Putri Permata Sari (MEDIKONS, 2022)
Abstract: This study aims to find out how the role of group guidance with the game Gobak Sodor for the children of the Aisyiyah II Orphanage Women's Orphanage in Surakarta. This research is a descriptive qualitative research. The subjects of this study were the children of the Aisyiyah II orphanage orphanage in Surakarta. Data collection techniques used are data from interviews, observations, and documentation. Interview technique is intended to obtain data in the form of direct statements from sources and participants, observation technique is intended to obtain data from participant activities, and documentation technique is intended to obtain written data and photo data of activities. The data analysis technique used is inductive, with 3 paths, namely data reduction, data presentation, and data verification. The results of this study explain how the role of group guidance services with the Gobak Sodor game technique in forming social characters in the Aiyiyah II Surakarta orphanage children. Judging from the provision of group guidance services with the Gobak Sodor game to participants, it had a good impact and gained an understanding that social character was important for participants. It is realized by the participants that social character is part of the participant's personality that must be formed in order to prepare for the future in order to have a superior character. Keywords: Group guidance; Gobak Sodor game; social character